SPME-GC-MS and Multivariate Analysis of Sensory Properties of Cheese in a Sack Matured with Probiotic Starter Cultures - Deni Kostelac (Food Technology and Biotechnology, 2020)
Research background. Cheese in a sack is a traditional cheese produced in Croatia. Types of cheese with similar production technology are made in other countries but chemical and microbiological composition varies between regions. Traditionally, cheese in a sack is produced without the addition of starter cultures. Addition of beneficial probiotic cultures to numerous dairy products has documented advantages. Effects that the addition of probiotic bacteria to traditional cheese have on aroma compounds and sensory properties have not been fully investigated. The aim of this study is to determine the sensory properties and differences in the aromatic profiles between cheese samples ripened in a lambskin sack, produced traditionally without the addition of any starter culture, or with the addition of probiotic bacteria. Experimental approach. In this study, cheese in a sack was produced with the addition of probiotic cultures Lactobacillus plantarum B and L. lactis ssp. lactis S1. During ripening volatile aroma compounds were analysed with a solid-phase microextraction gas chromatography-mass spectrometry. Sensory properties were evaluated by trained tasters who are familiar with the traditional taste of the cheese from a sack. The results of aroma composition and taste scores were then compared using factorial and principal component analyses. Results and conclusions. Chromatography showed differences in the composition of aroma compounds and the sensory properties between the cheese produced with Lactobacillus starter cultures and the control cheese, traditionally produced without a starter culture. The addition of probiotic cultures L. plantarum B and L. lactis ssp. lactis S1 resulted in products with better sensory properties and chemical profile of volatile aromatic compounds. Novelty and scientific contribution. This study investigates the usage of naturally present probiotic cultures as starter cultures in cheese in a sack production. Their effects on aroma profiles and sensory characteristics have been compared for the first time using factorial and principal component analyses.